Why are epilepsy mortality rates rising in the United States? A population-based multiple cause-of-death study - DeGiorgio, Christopher M (BMJ Open, 2020)
INTRODUCTION: Epilepsy mortality rates are rising. It is unknown whether rates are rising due to an increase in epilepsy prevalence, changes in epilepsy causes of death, increase in the lethality or epilepsy or failures of treatment. To address these questions, we compare epilepsy mortality rates in the USA with all-cause and all-neurological mortality for the years 1999 to 2017. OBJECTIVES: To determine changes in US epilepsy mortality rates versus all-cause mortality, and to evaluate changes in the leading causes of death in people with epilepsy. DESIGN: Retrospective population-based multiple cause-of-death study. PRIMARY OUTCOME: Change in age-adjusted epilepsy mortality rates compared with mortality rates for all-cause and all-neurological mortality. SECONDARY OUTCOME: Changes in the leading causes of death in epilepsy. RESULTS: From 1999 to 2017, epilepsy mortality rates in the USA increased 98.8%, from 5.83 per million in 1999 to 11.59 per million (95% CI 88.2%–110.0%), while all-cause mortality declined 16.4% from 8756.34 per million to 7319.17 per million (95% CI 16.3% to 16.6%). For the same period, all-neurological mortality increased 80.8% from 309.21 to 558.97 per million (95% CI 79.4%–82.1%). The proportion of people with epilepsy who died due to neoplasms, vascular dementia and Alzheimer’s increased by 52.3%, 210.1% and 216.8%, respectively. During the same period, the proportion who died due to epilepsy declined 27.1%, while ischaemic heart disease as a cause of death fell 42.6% (p<0.001). CONCLUSIONS: Epilepsy mortality rates in the USA increased significantly from 1999 to 2017. Likely causes include increases in all-neurological mortality, increased epilepsy prevalence and changes in the underlying causes of death in epilepsy, led by increases in vascular dementia and Alzheimer’s. An important finding is that ischaemic heart disease and epilepsy itself are declining as underlying causes of death in people with epilepsy.